2020
DOI: 10.3390/jcm9020587
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Right and Left Ventricular Longitudinal Function in Patients with Fibrotic Interstitial Lung Diseases

Abstract: Background: Left ventricular (LV) and right ventricular (RV) dysfunction is recognized in idiopathic pulmonary fibrosis (IPF). Little is known about cardiac involvement in non-idiopathic pulmonary fibrosis (no-IPF). This issue can be explored by advanced echocardiography. Methods: Thirty-three clinically stable and therapy-naive fibrotic IPF and 28 no-IPF patients, and 30 healthy controls were enrolled. Exclusion criteria were autoimmune systemic diseases, coronary disease, heart failure, primary cardiomyopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…There is evidence that the assessment of longitudinal strain by STE may help clinicians track changes in RV function with a relevant impact on disease management and outcome prediction [ 27 , 28 ]. In this regard, we previously reported that early reduction of RV strain was associated with clinical deterioration and was correlated with lung function impairment in patients affected by IPF [ 29 ]. As an emerging and attractive biomarker, RV-to-pulmonary circulation coupling is an indicator of the relationship between the RV contractility and its afterload; therefore, any perturbation of this interaction reflects early RV dysfunction, as previously shown in studies that invasive measured the pressure–volume loop-derived Ees/Ea ratio [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the assessment of longitudinal strain by STE may help clinicians track changes in RV function with a relevant impact on disease management and outcome prediction [ 27 , 28 ]. In this regard, we previously reported that early reduction of RV strain was associated with clinical deterioration and was correlated with lung function impairment in patients affected by IPF [ 29 ]. As an emerging and attractive biomarker, RV-to-pulmonary circulation coupling is an indicator of the relationship between the RV contractility and its afterload; therefore, any perturbation of this interaction reflects early RV dysfunction, as previously shown in studies that invasive measured the pressure–volume loop-derived Ees/Ea ratio [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the reduction of RV GWI, GCW, GWE and increase of GWW in HF patients compared to controls, they demonstrated that RV GCW is the only echocardiographic parameter associated with invasively measured stroke volume [ 65 ]. Therefore, MW seems to also be able to provide an all-around evaluation of the RV function, integrating information on contractility, dyssynchrony and pulmonary pressure, and overcoming the limitations of other standard parameters such as TAPSE, RV GLS or fractional area change [ 66 ]. Further and larger studies are needed to validate the application of MW software in studying the right chamber and extending its applicability in other clinical settings.…”
Section: Emerging Areas Of Applicationmentioning
confidence: 99%
“…Diabetic cardiomyopathy can be categorized as either having coronary artery disease or hypertension [4]. In addition to advanced glycation end products, atherosclerosis, microinfarctions in the subclinical stage, mitochondrial dysfunction, and lipotoxicity, several metabolic impairments contribute to diabetic cardiomyopathy [5] These impairments may affect both left ventilatory function (LV) and right ventilatory function (RV), due to their systematic nature [6]. It is believed that cardiovascular diseases represent a significant international public health burden due to the difficulty of evaluating heart contractile function in modern cardiology, which continues to be an issue [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to advanced glycation end products, atherosclerosis, microinfarctions in the subclinical stage, mitochondrial dysfunction, and lipotoxicity, several metabolic impairments contribute to diabetic cardiomyopathy [5] These impairments may affect both left ventilatory function (LV) and right ventilatory function (RV), due to their systematic nature [6]. It is believed that cardiovascular diseases represent a significant international public health burden due to the difficulty of evaluating heart contractile function in modern cardiology, which continues to be an issue [6]. In fact, the conventional parameter that describes left ventricular (LV) function, ejection fraction (EF), has considerable limitations due to its volumetric nature, suboptimal reproducibility, and a loss of ability to reflect local LV function.…”
Section: Introductionmentioning
confidence: 99%